Application of in-house nested polymerase chain reaction for rapid diagnosis of tuberculous pleural effusion - Amit Singh; Adesh Kumar; Vineet Chaturvedi; Pradeep Sharma (International Journal of Medical Research and Review, 2016)
Tuberculous pleural effusion (TPE) is a common manifestation of extrapulmonary tuberculosis and is the most common cause of pleural effusion in many countries. Conventional diagnostic tests for detection of Mycobacterium tuberculosis in pleural fluid or pleural tissue, have known limitations. Hence, there is need for a newer, rapid diagnostic tests. Molecular techniques, detecting DNA of M. tuberculosis in pleural fluid have better sensitivity and could be a potent tool for rapid diagnosis of tuberculous pleural effusion.Objective: To evaluate Nested PCR protocol targeting 38 kDa gene for rapid detection of M. tuberculosis complex in clinically suspected cases of TPE.Material and methods: A cross-sectional, prospective study was carried out at the tertiary care institute in a rural setup at western U.P. A total of 155 subjects with clinical suspicion of TPE enrolled during February 2015 to January 2016. About 10-20 ml of pleural fluid was collected and analysed for presence of M .tuberculosis by Z.N staining, culture on Lowenstein Medium (LJ), BacT/Alert 3D culture bottle and by Nested PCR targeting 38kDa gene of M. tuberculosis.Result: Off the 155 patients enrolled, M. tuberculosis was detected by AFB staining, LJ culture and BacT/Alert 3D system staining in 13 (8.4%), 45 (29%) and 72 (46.5%) respectively. Diagnostic sensitivity of nested PCR (nPCR) was 60.6% and among smear positive and culture negative samples, sensitivity was 100% while in smear negative, culture negative it was 29.2%.Conclusion: 38 kDa based nested PCR offers alternative robust approach for rapid and accurate detection of M .tuberculosis in paucibacillary tuberculous pleural effusion specimens.